Reboxetine Improves Auditory Attention and Increases Norepinephrine Levels in the Auditory Cortex of Chronically Stressed Rats - Pérez-Valenzuela, Catherine; Gárate-Pérez, Macarena F.; Sotomayor-Zárate, Ramón; Delano, Paul H.; Dagnino-Subiabre, Alexies (Frontiers in Neural Circuits, 2016)
Chronic stress impairs auditory attention in rats and monoamines regulate neurotransmission in the primary auditory cortex (A1), a brain area that modulates auditory attention. In this context, we hypothesized that norepinephrine (NE) levels in A1 correlate with the auditory attention performance of chronically stressed rats. The first objective of this research was to evaluate whether chronic stress affects monoamines levels in A1. Male Sprague–Dawley rats were subjected to chronic stress (restraint stress) and monoamines levels were measured by high performance liquid chromatographer (HPLC)-electrochemical detection. Chronically stressed rats had lower levels of NE in A1 than did controls, while chronic stress did not affect serotonin (5-HT) and dopamine (DA) levels. The second aim was to determine the effects of reboxetine (a selective inhibitor of NE reuptake) on auditory attention and NE levels in A1. Rats were trained to discriminate between two tones of different frequencies in a two-alternative choice task (2-ACT), a behavioral paradigm to study auditory attention in rats. Trained animals that reached a performance of ≥80% correct trials in the 2-ACT were randomly assigned to control and stress experimental groups. To analyze the effects of chronic stress on the auditory task, trained rats of both groups were subjected to 50 2-ACT trials 1 day before and 1 day after of the chronic stress period. A difference score (DS) was determined by subtracting the number of correct trials after the chronic stress protocol from those before. An unexpected result was that vehicle-treated control rats and vehicle-treated chronically stressed rats had similar performances in the attentional task, suggesting that repeated injections with vehicle were stressful for control animals and deteriorated their auditory attention. In this regard, both auditory attention and NE levels in A1 were higher in chronically stressed rats treated with reboxetine than in vehicle-treated animals. These results indicate that NE has a key role in A1 and attention of stressed rats during tone discrimination.